Air-Borne Particle Size Distribution of Wood Dust Emitted during Small Scale Forestry Operations - Biocca, Marcello; Pochi, Daniele; Gallo, Pietro; Fanigliulo, Roberto (Journal of Basic & Applied Sciences, 2023)
Practices such as tree felling, pruning, logging and chipping wood can produce significant amount of wood particles that can be inhaled by agricultural and forestry workers, triggering an important risk to the health of workers. Especially finest fractions of dust, less than 4 µm in diameter (the respirable fraction) may cause respiratory and dermal diseases, until to the risk of developing nose and sinus adenocancer. The aim of this work was to assess the particle size distribution of wood dust produced during chainsaw operations. In two separate trials (July and December), wood logs of three different species (Eucalyptus sp., Pinus radiata and Quercus cerris) were employed in cutting tests. Two chainsaws, one electric powered by batteries and one endothermic, were employed. To characterize the particle size distribution, samplings were carried out with a dust particle counter placed in the area surrounding the tests’ site. Results showed that the dust was characterized by a major fraction of fine particles around 0.3 µm (72% of the particles from 0.3 to 10 µm). The chainsaw with endothermic engine produced more fine dust of the electric one. Obtained amounts of inhalable wood dust were very variable in values, however attention should be paid to the exposure to wood dust considering potential risks, especially in case of long times of exposure.